2018
DOI: 10.5194/tc-12-2689-2018
|View full text |Cite
|
Sign up to set email alerts
|

Multi-channel and multi-polarization radar measurements around the NEEM site

Abstract: Abstract. Ice properties inferred from multi-polarization measurements, such as birefringence and crystal orientation fabric (COF), can provide insight into ice strain, viscosity, and ice flow. In 2008, the Center for Remote Sensing of Ice Sheets (CReSIS) used a ground-based VHF (very high frequency) radar to take multi-channel and multi-polarization measurements around the NEEM (North Greenland Eemian Ice Drilling) site. The system operated with 30 MHz bandwidth at a center frequency of 150 MHz. This paper de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Although the cross-polarised power anomaly has a 90 • ambiguity (Li et al, 2018), this ambiguity can be resolved if the corresponding co-polarised measurements detect anisotropic scattering (Brisbourne et al, 2019). We find that the symmetry axis orientation observed in our measurements aligns exactly with the observed present-day surface strain regime rather than the orientation of flow, at 250 • ±7 • (Fig.…”
Section: Methods Comparisons and Limitationssupporting
confidence: 54%
See 2 more Smart Citations
“…Although the cross-polarised power anomaly has a 90 • ambiguity (Li et al, 2018), this ambiguity can be resolved if the corresponding co-polarised measurements detect anisotropic scattering (Brisbourne et al, 2019). We find that the symmetry axis orientation observed in our measurements aligns exactly with the observed present-day surface strain regime rather than the orientation of flow, at 250 • ±7 • (Fig.…”
Section: Methods Comparisons and Limitationssupporting
confidence: 54%
“…By tracing the azimuthal minima in the cross-polarised power anomaly profiles through depth ( Fig. 2c) (Li et al, 2018) and resolving the observed 90 • ambiguity by identifying the azimuthal location of the centre of the quadrant patterns ( https://doi.org/10.5194/tc-2020-264 Preprint. Discussion started: 28 September 2020 c Author(s) 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaughan and others, 2006; Dall and others, 2010). These systems allow for the analysis of crystal-fabric orientation from polarization information (Doake and others, 2002; Fujita and others, 2003; Matsuoka and others, 2003; Eisen and others, 2007; Drews and others, 2012; Li and others, 2018; Wang and others, 2018; Jordan and others, 2019). This information can be used to constrain the depth distribution of the crystal orientation fabric along survey lines, enabling the investigation of processes occurring in ice masses, comparison to ice-dynamic models, and interpretation of particle-astrophysical observations (e.g.…”
Section: Systemsmentioning
confidence: 99%
“…As the depth of R1 rules out ice-density fluctuations, we attribute the unit to comprise a strong ice-crystal fabric, noting also that significant variability in crystal fabric is observed in the lower parts of West Antarctic ice cores (e.g. Gow and Williamson, 1976;Fitzpatrick et al, 2014), and that radar reflection anisotropy has been verified by ice core evidence from Antarctica and Greenland (Eisen et al 2007, Drews et al 2012Li et al 2018). The anisotropic layers cannot be due to directional roughness of layer reflectivity, as the anisotropy is unique to specific layers (Figures 6a and Supplementary Figures 1-4).…”
Section: Physical Explanations For Englacial Reflectionsmentioning
confidence: 81%